Photography, modernity and the governed in late-colonial Indonesia - Protschky, Susie (Amsterdam University Press, 2015)
This powerful study examines how contested notions of modernity, civilisation and being governed were envisioned through photography in early twentieth-century Indonesia when a reform programme known as the Ethical Policy was being implemented under the Dutch colonial regime. This is the first work to examine ethical ways of seeing through photography, a medium whose proliferation coincided with significant social and political change in colonial Indonesia.